Kajian Kepentingan Penerapan Teknologi Wearables dalam Meningkatkan Tahap Keselamatan Di Tapak Bina Di Negeri Johor - Mohd Azlizam , Nor Syazlin Izzati; Mohamed, Sulzakimin; Mohamed Aris, Nur Arzwin; Omar, Roshartini; Sarpin, Norliana (Research in Management of Technology and Business, 2024)
Wearables technology is a technology that can help in improving the safety level of workers in the construction site area. Where, without the comprehensive application of wearables technology and careful supervision, problems such as accidents at construction sites as well as problems in terms of project progress and cost. Therefore, a study that includes the objective of the study was conducted to examine the potential gained from the application of wearable technology that can help improve the level of worker safety in construction site areas. Studying the challenges in applying the use of wearable technology in Johor state construction sites that can improve the level of worker safety. Identify steps to implement the use of wearables technology in construction site areas to ensure their safety level increases. This study was conducted using a qualitative method which is an interview session with three respondents from different companies. This study achieves its goal by identifying the potential of wearables technology to improve worker safety on construction sites, explaining the challenges of applying the technology, and formulating measures to apply it effectively, including aspects of data security, worker involvement, pilot testing, as well as careful monitoring and enforcement. In conclusion, this study has been successfully conducted and has achieved the objectives of this study. Although there were some constraints such as changing the date for the interview and emergency features at the construction site, but in the end this study was successfully completed in addition to meeting all the research objectives where wearables can improve safety and communication between workers even though the cost may increase in its use.